2022
DOI: 10.1158/1078-0432.ccr-22-0384
|View full text |Cite
|
Sign up to set email alerts
|

EWS::FLI1 and HOXD13 Control Tumor Cell Plasticity in Ewing Sarcoma

Abstract: Purpose: Propagation of Ewing sarcoma requires precise regulation of EWS::FLI1 transcriptional activity. Determining the mechanisms of fusion regulation will advance our understanding of tumor progression. Here we investigated whether HOXD13, a developmental transcription factor that promotes Ewing sarcoma metastatic phenotypes, influences EWS::FLI1 transcriptional activity. Experimental Design: Existing tumor and cell line d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…With the inclusion of EWS/FLI mediated chromatin loops, we identified 193 genes that are dysregulated by a conserved EWS/FLI peak associated with a gained loop in EF-Endo versus EF-KD. These include genes that were previously shown to be EWS/FLI responsive and play important roles in tumor growth and/or metastasis in Ewing sarcoma, such as NKX2-2 ( 8 , 15 ), PPP1R1A ( 70 ), HOXD13 ( 71 ), FEZF1 ( 11 , 72 ), CCND1 ( 15 , 73 ) and CAV1 ( 74 ). We also identified target genes that code for surface proteins, such as SLC24A3 , NTNG1 , LINGO1 and PAPPA , reported as potential candidates for antibody-mediated therapies in Ewing sarcoma ( 75 , 76 ).…”
Section: Resultsmentioning
confidence: 99%
“…With the inclusion of EWS/FLI mediated chromatin loops, we identified 193 genes that are dysregulated by a conserved EWS/FLI peak associated with a gained loop in EF-Endo versus EF-KD. These include genes that were previously shown to be EWS/FLI responsive and play important roles in tumor growth and/or metastasis in Ewing sarcoma, such as NKX2-2 ( 8 , 15 ), PPP1R1A ( 70 ), HOXD13 ( 71 ), FEZF1 ( 11 , 72 ), CCND1 ( 15 , 73 ) and CAV1 ( 74 ). We also identified target genes that code for surface proteins, such as SLC24A3 , NTNG1 , LINGO1 and PAPPA , reported as potential candidates for antibody-mediated therapies in Ewing sarcoma ( 75 , 76 ).…”
Section: Resultsmentioning
confidence: 99%
“…These studies have shown that expression and transcriptional activity of the fusion varies among tumor cells and that cells exist along a transcriptional continuum from less to more mesenchymal states. Significantly, this heterogeneity is evident in tumor-derived cell lines and patient-derived xenografts (PDX) in vitro and in vivo and in patient tumor biopsies ( 17 , 22 , 33 , 34 ). Consistent with genetic knockdown studies, cells with higher EWS::FLI1 activity express proliferative signatures, while cells with lower transcriptional activity upregulate mesenchymal gene signatures and display enhanced metastatic potential ( 17 , 22 , 33 ).…”
Section: Characteristics Of the Ews::fli1 “High” And “Low” Cell Statesmentioning
confidence: 99%
“…Significantly, this heterogeneity is evident in tumor-derived cell lines and patient-derived xenografts (PDX) in vitro and in vivo and in patient tumor biopsies ( 17 , 22 , 33 , 34 ). Consistent with genetic knockdown studies, cells with higher EWS::FLI1 activity express proliferative signatures, while cells with lower transcriptional activity upregulate mesenchymal gene signatures and display enhanced metastatic potential ( 17 , 22 , 33 ). Elucidating the contribution of these distinct cell states to local and metastatic progression, treatment response, and relapse is an area of intense investigation in the field.…”
Section: Characteristics Of the Ews::fli1 “High” And “Low” Cell Statesmentioning
confidence: 99%
See 2 more Smart Citations